2010
DOI: 10.1038/ejhg.2010.166
|View full text |Cite
|
Sign up to set email alerts
|

Advanced age increases chromosome structural abnormalities in human spermatozoa

Abstract: This study explores the relationship between sperm structural aberrations and age by using a multicolor multichromosome FISH strategy that provides information on the incidence of duplications and deletions on all the autosomes. ToTelvysion kit (Abbott Molecular, Abbott Park, IL, USA) with telomere-specific probes was used. We investigated the sperm of 10 male donors aged from 23 to 74 years old. The donors were divided into two groups according to age, a cohort of five individuals younger than 40 and a cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 37 publications
2
22
0
1
Order By: Relevance
“…Martin and Rademaker [1987] have reported an increased level of structural abnormalities in sperm in the form of chromosome breaks in the sperm of older males. More recently, Templado et al [2011] also reported an increase in unbalanced structural rearrangements (especially duplications) in the sperm of older men, with larger chromosomes displaying a higher rate of abnormalities, contributing to the evidence of an age effect on the level of damage seen in human spermatozoa, which could be associated with chromosome breakage seen in human preimplantation embryos. In this study, the overall paternal age was 38 years.…”
Section: Discussionmentioning
confidence: 99%
“…Martin and Rademaker [1987] have reported an increased level of structural abnormalities in sperm in the form of chromosome breaks in the sperm of older males. More recently, Templado et al [2011] also reported an increase in unbalanced structural rearrangements (especially duplications) in the sperm of older men, with larger chromosomes displaying a higher rate of abnormalities, contributing to the evidence of an age effect on the level of damage seen in human spermatozoa, which could be associated with chromosome breakage seen in human preimplantation embryos. In this study, the overall paternal age was 38 years.…”
Section: Discussionmentioning
confidence: 99%
“…21 Templado et al 22 found a higher rate of structural abnormalities in the sperm of older males (6.6%) compared with younger males (4.9%). We have previously shown that non-recurrent reciprocal translocations have a strong paternal bias and are associated with a significant increase in paternal age.…”
Section: Discussionmentioning
confidence: 99%
“…Wholechromosome losses or gains, which are the most relevant type of aneuploidy in oocytes, have been reported to occur at a rate of 4-5% in human sperm (Templado et al, 2011b;Lu et al, 2012). Interestingly, when chromosomal errors are seen with advanced paternal age, it is generally structural rearrangements rather than numerical changes that are observed -this has been suggested to be due to errors arising during spermatogonial stem cell division in the adult testis (Templado et al, 2011a). By contrast, aneuploidy rates in human eggs can be about 60% or higher (Fragouli et al, 2011;Kuliev et al, 2011) (Fig.…”
Section: Introductionmentioning
confidence: 99%